Changes of compound hot and dry extremes on different land surface conditions in China during 1957–2018. (17th August 2020) - Feng, Yao; Liu, Wenbin; Sun, Fubao; Wang, Hong
Abstract: The co‐occurrence of hot and dry extremes (compound hot and dry extreme, CHDE) has attracted much attention due to the amplified impact on wildfire occurrence, agriculture production and human health. Most existing studies have reported the spatiotemporal variations of CHDE, changes in CHDE on different land surface conditions are barely discussed. The study investigated the spatial and temporal differences of CHDE over different regions and land covers in China during 1957–2018. On average over China, both day‐ and night‐time CHDEs have increased with a more rapid (2.6 times faster) and significant ( p  < .05) increasing trend in night‐time ones. Increasing trends are mainly distributed in north China with decreasing trends in central China. Moreover, increasing trends in night‐time mildly dry (0.07 per decade) and moderately hot (0.06 per decade) CHDEs are the largest among all dry and hot CHDEs. Regionally, the frequency of CHDE is the highest over the humid and sub‐humid regions for night‐ and day‐time CHDEs, but the lowest for both over the arid region. Meanwhile, CHDE has increased over the humid and sub‐humid regions in the recent decade but decreased over the arid region since 1957. For different land covers, the frequency of CHDE is the highest over forest but the lowest over grassland. Day‐time CHDEs of different hot magnitudes indicate the largest increasing trends over grassland caused by the largest increasing trends of day‐time heatwave. Significant ( p  < 0.05) increasing trends of day‐ and night‐time CHDEs over forest may increase the risks of tree mortality or forest fires after 2010 and larger increasing trends in night‐time CHDEs over urban may negatively impact human health. Abstract : Day‐ and night‐time compound extremes have increased with a more rapid and significant increasing trend in night‐time ones. An overall large increasing trend of compound extremes is detected over the humid and semi‐humid regions. Increasing trends in compound extremes are detected over forest and grassland. Spatial trends of day‐ (a) and night‐time (b) compound extremes (DCHDE and NCHDE), MK test (UF and UB, the primary vertical axis) and temporal variations (column charts, the secondary vertical axis) of DCHDE (c) and NCHDE (d) of 303 stations from 1957 to 2018. Crosses denote trends significant at 0.05 significance level. The inserted percentages denote the station ratios in each level of trend. Numbers in the brackets present the average trends (a, b) and frequency (c, d) of DCHDE and NCHDE of 303 stations.